Developing Reading Comprehension Modules to Facilitate Reading Comprehension among Malaysian Secondary School ESL Students - Javed, Muhammad; Lin, Siew Eng; Mohamed, Abdul Rashid (Eskişehir Osmangazi University, 2015)
The study aims to develop a set of 6 Reading Comprehension Modules (RCMs) for Malaysian ESL teachers to facilitate different reading abilities of ESL students effectively. Different skill categories were selected for developing the RCMs. This article describes how and why diverse texts of varying length were adopted and adapted from various authentic sources for ESL students having different reading abilities/bands. It also discusses how literal, reorganisation, and inferential questions were constructed appropriately based on the texts selected in the RCMs. Five experienced content/language experts validated the RCMs while eighty ESL students selected through purposive sampling from a secondary school from Penang, Malaysia participated in the pilot study for determining the reliability of the RCMs. The results of the pilot study revealed that the participants improved their scores gradually. Kuder and Richardson Formula 20 (KR-20) was employed to determine the internal consistency of the RCMs. The calculated values of RCMs ranged between 0.804 and 0.923 that indicate high reliability. The RCMs were standardised through a rigorous developmental process by using the Pebble in the Pond Model (Merril, 2002). We hope that the standardised RCMs would act as indicators for the ESL teachers to enhance ESL students' performance in reading comprehension.